Immune evasion in malaria: altered peptide ligands of the circumsporozoite protein. - Plebanski, M; Lee, E; Hill, A (1997)
T cells are central to immunity in malaria. CD4+ helper T cells favour the generation of high-affinity antibodies that are effective against blood stages and they are necessary to establish immunological memory. The intrahepatic stage of infection can be eliminated by specific CD8+ cytotoxic T cells (CTL). Cytokines secreted by CD4+ T cells may also contribute to liver stage immunity. Evolution has selected varied mechanisms in pathogens to avoid recognition by T cells. T cells recognize foreign epitopes as complexes with host major histocompatibility (MHC) molecules. Thus, a simple form of evasion is to mutate amino acid residues which allow binding to an MHC allele. Recently, more sophisticated forms of polymorphic evasion have been described. In altered peptide ligand (APL) antagonism, the concurrent presentation of particular closely related epitope variants can prevent memory T cell effector functions such as cytotoxicity, lymphokine production and proliferation. In immune interference, the effect of the concurrent presentation of such related epitope variants can go a step further and prevent the induction of memory T cells from naive precursors. The analysis of immune responses to a protein of P. falciparum, the circumsporozoite protein (CSP), indicates that the malaria parasite may utilize these evasion strategies.